(untitled) - Brines, Russell (Philadelphia, 1948)
Russell Brines here provides a first-hand survey of the most remarkable military occupation in history, an occupation rich in drama, full of anecdotes and color, holding deepest concern to all of us.
Keywords: Reconstruction (1939-1951),Japan; Allied occupation, 1945-1952; Japan,History